Gedagtes oor begeerte en mites in reklamekommunikasie - Moller, Jere; Van Niekerk, Angelique (Department of Communication Science, University of the Free State, 2006)
Change in the world is reflected in almost every aspect of our lives - how we live, eat, communicate. For reasons of authentication the mass media use real people in real life settings to convince real people to buy or use a product or service. For this reason it can be argued that the mass media (especially advertisements) offer a particular view of society. It is within such a specific system of belief that the mass media sells certain desires. Without a specific system of belief it is not possible to sell certain desires, for example: fitness (not sport shoes), or beauty (not lipstick). This view of the world offered by advertisements is unique and therefore advertising can be identified with its unique characteristics and conventions within the bigger media world. The research focus is on the relevance of disciplines such as semantics and pragmatics, and constructs such as denotation, connotation, desire and myth in analysing printed advertising communication and to identify marketing communication as genre type with unique conventions and shared knowledge.
Keywords: Mass media; Advertisements; Advertising communication; Marketing communication